From Disparity to Harmonisation of Construction Industry Payment Legislation in Australia: A Proposal for a Dual Process of Adjudication based upon Size of Progress Payment Claim - Jeremy Coggins (Construction Economics and Building, 2011)
Since the introduction of the Building and Construction Industry Security of Payment Act into New South Wales in 1999, construction industry payment legislation has progressively been enacted on a jurisdiction-by-jurisdiction basis throughout Australia. Of the eight Australian Acts, two distinct legislative models can be discerned – what have been termed the ‘East Coast’ and ‘West Coast’ models. This article compares the two models with respect to their payment systems and adjudication schemes, procedural justice afforded, incursion upon freedom of contract, uptake rates and efficiency. From this comparison, the strengths and weaknesses of the two models are identified. Finally, a dual process of adjudication based on progress payment claim size is proposed for a harmonised model, developed from previous proposals put forward by other authors, which aims to combine the strengths of the two existing models.